7-Foot Diameter Drilled Shafts In Weathered Rock: Design, Load Testing, And Construction - Aly M. Mohammad (Deep Foundations Institute, 2003)
The design of large diameter drilled shafts in weathered rock has always presented a challenge to the foundation engineers. Degree of weathering and load transfer mechanism through the rock are essential elements required for the design. From the Contractor's perspective specifying the right equipment and estimating the rate of drilling in the weathered rock are key elements for successful construction. The Delaware River Tramway Project has provided an opportunity to address the design and construction of drilled shafts in weathered rock. The Tramway, supported by twin 300-foot towers, will shuttle eight-person gondolas across the Delaware River in about four minutes. Each tower, founded on four high capacity drilled shafts, is designed to resist large axial and lateral loads. At the New Jersey tower, each 7-foot diameter shaft extends 145 feet deep and terminates in weathered Mica Schist. The shafts are situated in the Delaware River where the mud line is approximately 20 feet below Mean Low Water. Below the mud line, there exists a very soft, 20-foot thick layer of organic silt, followed by a 40-foot thick dense sand stratum. Below these sand and silt strata, a 70-foot thick layer of weathered Mica Schist underlies the entire site. Both skin friction and end bearing in the weathered rock stratum were utilized in the analysis to compute the axial capacity. AASHTO and the PennDOT design methodologies were utilized independently during design of the drilled shafts to verify the design. The drilling of large diameter drilled shafts embedded into weathered rock and situated in a marine environment provided a unique challenge in the construction. A permanent steel casing was installed for a specified depth and proper equipment was used to drill and keep the shaft open through the weathered rock. In addition, a 5000 kip Osterberg load test was performed on one shaft to verify design assumptions and confirm the shaft capacity. The results of the test were utilized to establish load transfer characteristics within the weathered rock and to develop foundation design parameters to be used for the remaining shafts.